Teachers’ Perception Towards Peer-Tutoring Strategies in Social Studies in Edo State - Eguagie, Osagie (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigated Social Studies teachers’ perceptions of peer-tutoring strategies in Upper Basic Schools in Edo State, Nigeria. The study was guided by four research questions and three hypotheses. Adopting a correlational survey research design, the study examined teachers’ level of awareness of peer-tutoring strategies, their perceived effectiveness, the extent of implementation in classrooms, and the challenges associated with their adoption. The population comprised all Social Studies teachers in public Upper Basic Schools across the three senatorial districts of Edo State. A multi-stage sampling technique was used to select a representative sample of 350 teachers. Data were collected using a structured, validated, and reliable instrument titled “Teachers’ Perception of Peer-Tutoring Strategies Questionnaire (TPPTSQ).” Descriptive statistics (mean and standard deviation) and inferential statistics (Independent Samples t-test and Pearson Product Moment Correlation Coefficient) were employed to analyze the data at a 0.05 level of significance. Findings revealed that teachers were generally aware of peer-tutoring strategies and perceived them as beneficial to student learning outcomes. However, the level of classroom implementation was moderate due to challenges such as overcrowded classrooms, inadequate training, and lack of administrative support. The study found no significant gender difference in teachers’ awareness of peer-tutoring strategies. Significant relationships were established between the extent of implementation and student academic performance, as well as between implementation and the challenges faced by teachers. The study recommends continuous professional development, institutional support, and strategic interventions to promote the effective use of peer-tutoring strategies in Social Studies instruction.